2021
DOI: 10.25259/sni_557_2021
|View full text |Cite
|
Sign up to set email alerts
|

Variations and management for patients with craniocervical junction arteriovenous fistulas: Comparison of dural, radicular, and epidural arteriovenous fistulas

Abstract: Background: Craniocervical junction arteriovenous fistulas (CCJAVFs) are known to be rare, but variations and clinical behaviors remain controversial. Methods: A total of 11 CCJAVF patients (M: F=9:2, age 54–77 years) were investigated. Based on the radiological and intraoperative findings, they were categorized into three types: dural AVF (DAVF), radicular AVF (RAVF), and epidural AVF (EDAVF). Results: There were four symptomatic patients (subarachnoid hemorrhage in two, myelopathy in one, and tinnitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
(52 reference statements)
0
17
0
Order By: Relevance
“… 6–8 Recent developments in various neuroradiological modalities and accumulation of surgical experience have led to the identification of radicular AVF on the spinal nerves located between the spinal cord and dura in which radiculomeningeal and pial feeders connect with the radicular vein at the same fistulous point. 9 , 10 In Case 2 of our report, radicular AVF was ruled out based on the lack of a fistulous point or feeders from the radiculomeningeal artery on the nerve root demonstrated by intraarterial ICG videoangiography. Hiramatsu et al classified CCJ AVF into five subgroups.…”
Section: Discussionmentioning
confidence: 91%
“… 6–8 Recent developments in various neuroradiological modalities and accumulation of surgical experience have led to the identification of radicular AVF on the spinal nerves located between the spinal cord and dura in which radiculomeningeal and pial feeders connect with the radicular vein at the same fistulous point. 9 , 10 In Case 2 of our report, radicular AVF was ruled out based on the lack of a fistulous point or feeders from the radiculomeningeal artery on the nerve root demonstrated by intraarterial ICG videoangiography. Hiramatsu et al classified CCJ AVF into five subgroups.…”
Section: Discussionmentioning
confidence: 91%
“…A craniocervical junction is a rare AVF lesion that accounts for 1% to 2% of intracranial or spinal AVFs 1 , 4 and mainly occurs in middle-aged men. 1 , 2 , 6 , 7 CCJAVFs have a wide range of clinical presentations, including acute SAH, 8–11 myelopathy, 12 intramedullary hemorrhage, 2 brainstem dysfunction, 6 , 13–15 and radiculopathy. 3 Our patient had respiratory disorders and tetraparesis after admission and completely recovered after treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Several studies have suggested that venous hypertension may be associated with CCJAVF. 2 , 17 Another possible etiology is thrombosis or congestion of the internal dural vein due to bone fracture or postoperative fibrosis causing an abnormal shunt. 22 In the present case, SAH was probably caused by ascending intracranial drainage, but the AVF mainly drained into the epidural plexus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations